Long-lifespan lithium–metal batteries obtained using a perovskite intercalation layer to stabilize the lithium electrode. Issue 18 (28th April 2020) - Kaisar, Nahid; Singh, Anupriya; Yang, Po-Yu; Chen, Yu-Ting; Li, Shenghan; Pao, Chun-Wei; Jou, Shankay; Chu, Chih-Wei
Abstract : Because it has the highest specific capacity and lowest reduction potential among the elements, as well as a low density, lithium (Li) metal has been the most practical anode material for high energy density lithium-ion batteries. Abstract : Because it has the highest specific capacity and lowest reduction potential among the elements, as well as a low density, lithium (Li) metal has been the most practical anode material for high energy density lithium-ion batteries. Nevertheless, Li plating and stripping can lead to the uncontrolled growth of mossy dendrites, resulting in poor coulombic efficiency and short-circuiting of the cells. Here, we demonstrate δ-CsPbI3 as an electrochemical intercalation layer, fabricated through an inexpensive and facile spray-coating method, that stabilizes Li electrodes for Li–metal batteries. Experimental and density functional theory studies confirmed that Li + ions can be intercalated electrochemically into δ-CsPbI3 (forming Li:CsPbI3 ), thereby increasing the conductivity and avoiding dendrite formation, resulting in improved ion migration, stabilized electrodeposition, and the maintained integrity of the solid–electrolyte interface. Electrochemical testing of a Li:CsPbI3 symmetric cell revealed dendrite-free plating after 1000 h at a current density of 1 mA cm −2 and discharge capacity of 1 mA h cm −2 . With an intercalation layer on a Li–metal anode, the Li–S full cell configuration displayed an initial specific capacity of 823 mA h g −1 with a decay rate of approximately 0.035% per cycle and a coulombic efficiency of approximately 100% throughout 1000 cycles at a 1C rate. Using this new concept, we have obtained stable Li–metal anodes for high energy density batteries, potentially opening up new approaches for preparing safe Li–metal batteries.